(untitled) (American Journal of Islam and Society, 2010)
The latest estimate by Afghan expert Gilles Dorronsoro (International Herald Tribune, 15 September 2010) states that no state structure remains in 80 percent of Afghanistan’s districts, that the Taliban are rapidly filling the vacuum, that the NATO surge in the south has failed, and that the allies should negotiate a settlement with them in order to achieve what assurances they can about discouraging the presence of al-Qaeda before it is too late. This book explains why such a limited success is the likely outcome of NATO’s attempt to build a working central Afghan state. It contains essays by ten leading scholars in the field who met at a conference in 2004. Most of the papers have been extended to a cut-off date of 2007. The book sets out to answer several questions: Are the Taliban, usually considered a militantly traditionalist movement, in fact a new phenomenon in Afghan history? Are they no more than a foreign creation, an instrument of Pakistan’s geopolitical interests in a post-cold war world? At the same time, given their utopian theology that looks back to an imagined period of early Islamic purity, should they be seen as essentially “medieval” and “antimodern”? Are these sufficient characterizations of this extraordinarily effective movement, or should more attention be paid to other factors, such as the long history of state-society relations in Afghanistan and how they have interacted with the great powers? ...